Doing meta-analysis with R a hands-on guide - Harrer, Mathias; Cuijpers, Pim 1956-; Furukawa, Toshi A.; Ebert, David Daniel 1979- (CRC Press, 2022)
"This book serves as an accessible introduction into how meta-analyses can be conducted in R. Essential steps for meta-analysis are covered, including pooling of outcome measures, forest plots, heterogeneity diagnostics, subgroup analyses, meta-regression, methods to control for publication bias, risk of bias assessments and plotting tools. Advanced, but highly relevant topics such as network meta-analysis, multi-/three-level meta-analyses, Bayesian meta-analysis approaches, SEM meta-analysis are also covered. A companion R package, dmetar, is introduced in the beginning of the guide. It contains data sets and several helper functions for the meta and metafor package used in the guide"--
Includes bibliographical references and index
Keywords: Metaanalyse; R -- Programm; Meta-analysis; R (Computer program language); Einführung